(untitled) (Cambridge, 2013)
The antiviral therapeutic area continues to rapidly generate meaningful new chemical entities; for example, for HIV alone more than 25 drugs have been approved, and in the next few years many individual drugs and single tablet regimens will be approved for the treatment of hepatitis C virus infection. The increasing success in the antiviral area could be due to targeting drugs at "non-self" genomes and to the patient population that is tolerant of manageable side effects and adaptable to inconvenient dosing.
Keywords: Drug development,Antiviral agents.,Virus diseases,Tác nhân chống vi rút.,Bệnh vi rút; Chemotherapy.,Hóa trị liệu.